CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon
MyQuestionIcon
0
You visited us 0 times! Enjoying our articles? Unlock Full Access!
Question

If f(x) = x - 1 ÷ x + 1 then f(2x) in terms of f(x) is?

Open in App
Solution


∵ ƒ(x) = ( x - 1 ) / ( x + 1 ) ............ (1)

∴ ( x + 1 ). ƒ(x) = x - 1

∴ x. ƒ(x) + ƒ(x) = x - 1

∴ x. ƒ(x) - x = - 1 - ƒ(x)

∴ x. [ ƒ(x) - 1 ] = - [ 1 + ƒ(x) ]

∴ x = [ 1 + ƒ(x) ] / [ 1 - ƒ(x) ] .................. (2)
_________________________

∴ from (1),

ƒ(2x) = [ (2x) - 1 ] / [ (2x) + 1 ]

. . . . .= { 2( [1+ƒ(x)] / [1-ƒ(x)] ) - 1 } / { 2( [1+ƒ(x)] / [1-ƒ(x)] + 1 }

. . . . .= { 2[ 1 + ƒ(x) ] - [ 1 - ƒ(x) ] } / { 2[ 1 + ƒ(x) ] + [ 1 - ƒ(x) ] }

. . . . .= { 2 + 2.ƒ(x) - 1 + ƒ(x) } / { 2 + 2.ƒ(x) + 1 - ƒ(x) }

. . . . .= [ 1 + 3.ƒ(x) ] / [ 3 + ƒ(x) ]
please read carefully
hope you understand this
like if you are satisfied

flag
Suggest Corrections
thumbs-up
1
Join BYJU'S Learning Program
similar_icon
Related Videos
thumbnail
lock
Some Functions and Their Graphs
MATHEMATICS
Watch in App
Join BYJU'S Learning Program
CrossIcon